Hyperthyroidism in four guinea pigs: clinical manifestations, diagnosis, and treatment. (31st July 2013) - Künzel, F.; Hierlmeier, B.; Christian, M.; Reifinger, M.
<x xml:space="preserve">Abstract</x> Hyperthyroidism was diagnosed in four guinea pigs by demonstration of an increased serum total thyroxine concentration. The main clinical signs were comparable with those observed in feline hyperthyroidism and included weight loss despite maintenance of appetite and a palpable mass in the ventral cervical region. Three animals were treated successfully with methimazole for between 13 and 28 months. Clinical signs and regular measurement of circulating total thyroxine concentrations appear to be convenient parameters for monitoring response to medical therapy.